Teaching of infection control in undergraduate courses in health sciences: opinion of experts - Massaroli, Aline; Martini, Jussara Gue; Moya, José Luis Medina; Bitencourt, Julia Valéria de Oliveira Vargas; Reibnitz, Kenya Schmidt; Bernardi, Mariely Carmelina (Revista Brasileira de Enfermagem, 2018)
ABSTRACT Objective: To know the perception of expert professionals in infection control and prevention on the teaching of skills for the prevention and control of infections related to health care in undergraduate courses in Health Sciences. Method: We used the Delphi technique, developed in four sequential rounds. Thirty-one nurses and eight physicians participated in the study. Qualitative data were analyzed through content analysis; the quantitative ones, from the descriptive statistics. Results: The importance of the courses has had teachers with expertise in infection control and prevention added to arguments about the development of the subject in the curricula by means of a specific subject or as a transversal theme. Conclusions: In order to cover the complexity of the elements that are interconnected for professional training, teaching must be based on pedagogical strategies that provoke reflection in students, encouraging them to develop critical thinking about their experiences. RESUMO Objetivo: Conhecer a percepção dos profissionais com expertise em prevenção e controle de infecção sobre o ensino das competências para a prevenção e o controle de infecções relacionadas à assistência à saúde nos cursos de graduação da área da saúde. Método: Utilizou-se a técnica Delphi, desenvolvida em quatro rodadas sequenciais. Participaram do estudo 31 enfermeiros e oito médicos. Os dados qualitativos foram analisados por meio da análise de conteúdo; os quantitativos, a partir da estatística descritiva. Resultados: Emergiu a importância de os cursos contarem com docentes com expertise em prevenção e controle de infecções. Somada a argumentações sobre o desenvolvimento do tema nos currículos por meio de uma disciplina específica ou como tema transversal. Conclusões: Para abranger a complexidade dos elementos que se interligam para a formação profissional, o ensino deve pautar-se em estratégias pedagógicas que instiguem a reflexão no estudante, estimulando-o a desenvolver o pensamento crítico sobre suas vivências. RESUMEN Objetivo: Conocer la percepción de los profesionales con experiencia en prevención y control de infección sobre la enseñanza de las competencias para la prevención y control de infecciones relacionadas a la asistencia a la salud en los cursos de graduación del área de la salud. Método: Se utilizó la técnica Delphi, desarrollada en cuatro rondas secuenciales. Participaron del estudio 31 enfermeros y 8 médicos. Los datos cualitativos fueron analizados por medio del análisis de contenido y los cuantitativos, a partir de la estadística descriptiva. Resultados: Ha surgido la importancia de que los cursos tengan docentes con experiencia en prevención y control de infecciones. Sumada a las argumentaciones sobre el desarrollo del tema en los currículos por medio de una disciplina específica o como tema transversal. Conclusiones: Para abarcar la complejidad de los elementos que se interconectan para la formación profesional, la enseñanza debe guiarse en estrategias pedagógicas que instiguen la reflexión en el estudiante, estimulándolo a desarrollar el pensamiento crítico sobre sus vivencias.